Leadership Coaching Techniques Utilized by High School Principals - Marlon R Valdez; Dr Phillip G Queroda (ASEAN Multidisciplinary Research Journal, 2019)
This study was administered to determine the techniques utilized by public high school principals in leadership coaching. Quantitative-descriptive research design was used in the study. The respondents comprise of high school principals from the Department of Education (DepEd) Division Offices of Pangasinan, Philippines and were determined thru stratified random sampling. A validated questionnaire was used as a tool in gathering the data. Experts in the field of leadership coaching served as validators. Average weighted mean, frequency counts, percentages, and Chi-square statistics were used as statistical tools in analysing the data gathered. Results found out that high school principals highly utilized leadership coaching techniques. Further, the extent of utilization of leadership coaching techniques utilized by high school principals has no effect to their profile variables.